Closing a chapter: The end of student life / Nur Ainin Sofiya Mohamad Irwan - Mohamad Irwan, Nur Ainin Sofiya (Faculty of Pharmacy, 2023)
The time has come, it feels surreal. October 2022 was the day I stepped into my senior year; it was both thrilling and nostalgic. The lectures were even delivered differently in terms of clinical applications, future career prospects, and entrepreneurshipwise; all which covered pharmaceutical care. As final year students, we began to involve with the community and had opportunities to interact with real patients. Besides that, we also had presentations, attended career exhibitions and motivational talks from experts, did mocks for job interviews, gave patient counseling under lecturers’ supervision, reviewed and answered queries of clinical cases, joined feedback sessions from lectures and courses lab, attached in various hospital pharmacy departments and completed 7 OSCEs. We even pitched for our own pharmacy and many others!